Anterior Peripheral Rim Instability Is Prevalent in Young, Skeletally Immature Patients With Discoid Lateral Meniscus and Has Favorable Postoperative Outcomes - Steven Maxwell Henick, M.D.; Zachariah Samuel, B.S.; Joseph Nicholas Charla, B.S.; Emily Ferreri, B.S.; Emmanuel Mbamalu, B.S.; Edina Gjonbalaj, B.S.; Leila Mehraban Alvandi, Ph.D.; Jacob Foster Schulz, M.D.; Eric Daniel Fornari, F.A.O.A., M.D.; Mauricio Drummond, Jr., M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To report the prevalence and patient characteristics of anterior peripheral rim instability (PRI) in patients <21 years of age with symptomatic discoid lateral meniscus (DLM) requiring operative intervention and to compare preoperative magnetic resonance imaging (MRI) with arthroscopic findings and patient-reported outcomes (PROs) after arthroscopic treatment of anterior compared with nonanterior PRI. Methods: A retrospective review was performed at a single academic institution between 2012 and 2022. Patients were <21 years old and underwent operative DLM management with a minimum follow-up period of 2 years. Patients were divided into 2 groups: anterior PRI (isolated anterior PRI and anterior combined with posterior PRI) and nonanterior PRI (nonanterior PRI designated as isolated posterior or no PRI). Data collection included demographics, clinical presentation, MRI results, arthroscopic findings, reoperation rates, complications, and PROs. Results: Forty-four patients were included, 22 in the anterior PRI group and 22 in the nonanterior PRI group. Anterior PRI prevalence was 50% in this cohort. Patients in the anterior PRI group were younger (10.77 ± 3.07 vs 13.002 ± 3.39; P = .028) and more likely skeletally immature (16 vs 8; P = .034). Extension deficit (P = .486) did not differ significantly between the groups. MRI was less sensitive for detecting anterior PRI compared with posterior PRI (72.2% vs 95.0%; P = .140). Patients with anterior PRI showed significant improvements in postoperative PROs (Pedi- International Knee Documentation Committee 54.23 vs 89.65; P = .0006) after 6.1 years of average follow-up, achieving good-to-excellent scores that did not significantly differ between groups. Conclusions: The prevalence of anterior PRI in symptomatic DLM is 50% in our cohort and is more likely to cause symptoms in skeletally immature and younger patients. It more commonly presents with posterior PRI (59%) than as an isolated entity (41%). Arthroscopic outside-in repair yields good-to-excellent PROs and low complication and reoperation rates after mean 6.1 years of follow-up. Level of Evidence: Level III, therapeutic retrospective, cohort study.